In vitro effect of anodization of titanium abutments on their tensile bond strength to implant-supported lithium disilicate all-ceramic crowns - Hamed Karimi Pour; Homeira Ansari; Azita Mazaheri Tehrani (Wolters Kluwer Medknow Publications, 2023)
Background: The retention of cement-retained implant-supported restorations can be affected by surface treatments such as anodizing. This study aimed to assess the effect of the anodization of titanium abutments on their tensile bond strength to implant-supported lithium disilicate (LDS) all-ceramic crowns. Materials and Methods: This in vitro, experimental study was conducted on 26 straight abutments in two groups of anodization and control. In the anodization group, seven flat 9 V batteries connected in series were used to generate 64 V energy. A glass container was filled with 250 mL of distilled water, and 1 g of trisodium phosphate was added to it to create an electrolyte solution. The anode was then disconnected and the abutment was rinsed with acetone and deionized water. The surface roughness of abutments was measured by a profilometer. The abutments were scanned by a laboratory scanner, and maxillary central incisor monolithic crowns were fabricated by inLab SW18 software. The crowns were seated on the abutments and temporarily cemented with TempBond. They were then incubated in artificial saliva and subjected to 5000 thermal cycles. The tensile bond strength of crowns was then measured. Data were analyzed by the Student's t-test and Mann-Whitney U-tests (α =0.05). Results: The mean bond strength was significantly higher in anodized abutments (P = 0.003). The surface roughness of anodized abutments was slightly, but not significantly, higher than that of the control group (P > 0.05). The frequency of adhesive failure was almost twice higher in anodized abutments. Conclusion: Anodization of titanium abutments significantly improved their tensile bond strength to implant-supported LDS all-ceramic crowns.